2008
DOI: 10.1007/s10856-008-3385-6
|View full text |Cite
|
Sign up to set email alerts
|

ESEM evaluations of muscle/nanoparticles interface in a rat model

Abstract: In order to examine the influence that shape and chemistry of different materials have on the incitement of a tissue reaction, we implanted five materials (the two metals Ni and Co, the two ceramics TiO2 and SiO2, and the polymer poly vinyl-chloride) as nanoparticles or bulk, in the dorsal muscles of 50 rats. After 6 or 12 months, rats were euthanized and the implanted materials were excised together with the surrounding tissue. After a first histological evaluation, the specimens were prepared for environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…So far, most of the work on tissue distribution of nanoparticles has been restricted to rodents (Kim et al 2006;Gatti et al 2008;Cho et al 2009;Park et al 2009;Xie et al 2010;Liu et al 2011). The present study, as far as we know, is the first report describing silicon-based quantum dots distribution in fish white muscle.…”
Section: Discussionmentioning
confidence: 70%
“…So far, most of the work on tissue distribution of nanoparticles has been restricted to rodents (Kim et al 2006;Gatti et al 2008;Cho et al 2009;Park et al 2009;Xie et al 2010;Liu et al 2011). The present study, as far as we know, is the first report describing silicon-based quantum dots distribution in fish white muscle.…”
Section: Discussionmentioning
confidence: 70%
“…System. Two studies investigated the biological tolerance of TiO 2 NPs when implanted in rat living tissues [143,144] (Table 8). Interest in this type of research emerges from the promising utilization of NPs in numerous fields of medicine and the not fully understood potential reactions at the tissue-material interface.…”
Section: Musculoskeletalmentioning
confidence: 99%
“…Their results showed that the nanoscale metals have carcinogenic effect, while the bulk materials only cause a foreign-body reaction. Their ESEM observations verified the agglomeration of all the NPs, especially for Ni which formed microsize particles that can be attributed to the tendency of NPs to agglomerate and also possible interactions with the tissue [38].…”
Section: Microscopy Techniquesmentioning
confidence: 82%